Sociodemographic Characteristics and Stress of People from Spain Confined by COVID-19 - Susana Rodríguez; Antonio Valle; Isabel Piñeiro; Carolina Rodríguez-Llorente; Estefanía Guerrero; Ludmila Martins (MDPI AG, 2020)
This study responds to the need to explore the individual characteristics that may help us to understand the levels of stress involved in the significant COVID-19-related restrictions to people's daily lives. In order to understand levels of stress and stress control during the COVID-19 confinement, 1269 people from Spain (17.5% men) aged between 18 and 70 completed the Perceived Stress Scale (PSS-14). The results indicated that people aged under 40, and especially those under 25, women, and those on low incomes reported higher rates of confinement stress. The nature of where people live, and their working situation during confinement also contributed to people's stress response, although with lower levels of impact. In this context, our study suggests that the levels of stress in those who combine remote working with in situ working were lower than those who had other working conditions. Our study contributes significant information to understanding the effects of confinement, and its results may be used to inform intervention tools and programs.